KAJIAN YURIDIS REGULASI PERLINDUNGAN HUKUM TERHADAP PENYALAHGUNAAN DATA PRIVASI DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 27 TAHUN 2022 TENTANG PELINDUNGAN DATA PRIBADI - Lilik Prihatin; Muhammad Achwan; Citra Candra Dewi (UNES Law Review, 2023)
Identical personal information, often referred to as personal data, is information that must be kept confidential to avoid the risk of misuse by irresponsible parties or the interests of other people. The study discussed is a juridical study on legal protection against misuse of privacy data in the Personal Data Protection Act No. 27 of 2022. This type of research is normative legal research which adopts a legal approach that uses secondary data types, to obtain information that is appropriate to the research topic. Data leak cases experienced by Indihome, PLN, users of the Ministry of Health and Health's e-HAC application related to cases of data leaks for BPJS, BRI Life customers, KPU final voter lists, Tokopedia users, pre-employment cards requiring KTP selfies, are an illustration where personal data information is the privacy of every individual whose data must be protected. So that legal protection can be accommodated in regulations or regulations in the Banking Law, Telecommunications Law, Consumer Protection Law, Human Rights Law, Public Information Disclosure Act, Health Law, Population Control Law , Electronic Information and Electronic Transaction Law. Privacy protection is also regulated in Law no. 27/2022 concerning personal data protection, which regulates the prohibition of using personal data that harms other people so that they can be subject to sanctions. Because the protection of individual statistics are a human right related to the protection of individuals, it is necessary to establish a legal basis for the protection of personal statistics based on the 1945 Constitution of the Republic of Indonesia (UUD 1945).